2021
DOI: 10.3390/nu13030855
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fucose Affects Macrophage Polarization and Reproductive Performance in Mice

Abstract: Intestinal mucus protects epithelial and immune cells from the gut resident microorganisms, and provides growth-promoting factors as mucus-derived O-glycans for beneficial bacteria. A lack of intestinal protective mucus results in changes in the commensal microflora composition, mucosal immune system reprogramming, and inflammation. Previous work has shown that fucose, the terminal glycan chain component of the intestinal glycoprotein Mucin2, and fucoidan polysaccharides have an anti-inflammatory effect in som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 71 publications
1
7
0
1
Order By: Relevance
“…However, in our previous study, L-fucose improved inflammation neither in acute, nor in chronic DSS-induced colitis [27]. In our previous work we showed the importance of the immune context for the effect of L-fucose on macrophage polarization and pregnancy outcome: two prototypical mouse strains with Th1-and Th2-type of immune response demonstrated the opposite effect of L-fucose treatment [17]. These data suggest that L-fucose effects on inflammation are highly dependent on the current immune state and microenvironment which in in vivo context includes immune-system-microflora interactions.…”
Section: Plos Onementioning
confidence: 83%
See 1 more Smart Citation
“…However, in our previous study, L-fucose improved inflammation neither in acute, nor in chronic DSS-induced colitis [27]. In our previous work we showed the importance of the immune context for the effect of L-fucose on macrophage polarization and pregnancy outcome: two prototypical mouse strains with Th1-and Th2-type of immune response demonstrated the opposite effect of L-fucose treatment [17]. These data suggest that L-fucose effects on inflammation are highly dependent on the current immune state and microenvironment which in in vivo context includes immune-system-microflora interactions.…”
Section: Plos Onementioning
confidence: 83%
“…Being the terminal glycan chain component of the glycoprotein Mucin2, orally administered L-fucose could play an important role in modulation of intestine microenvironment in Mucin2-deficient mice. L-fucose has been shown to inhibit macrophage M1 polarization [16,17]. The resolution of intestinal inflammation and mucosal healing is under the control of local macrophages which are divided into two categories: inflammatory recruited macrophages differentiated from monocytes which migrate to the cite of inflammation (M1 type) and resident macrophages with tolerant phenotype which produce anti-inflammatory cytokines such as IL-10 and TGF-β (M2 type).…”
Section: Introductionmentioning
confidence: 99%
“…The only enriched DEP was alpha-(1,6)-fucosyltransferase, which involved in the synthesis of active ribose, providing raw materials for the formation of precursor sugar nucleotides and participating in the synthesis and assembly of fucose [ 37 ]. Recent research has highlighted the involvement of fucose in reproductive performance in mice [ 38 ]. These findings further suggested that carbohydrate metabolism had a crucial part in oogenesis in M. nipponense and was perhaps major source of energy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, fucose plays an important role in immunoregulation of renal disease by reducing the deposition of complement C3 on renal tubules and infiltration of immune cells ( 49 ), which is beneficial to the therapeutic intervention of IgAN ( 50 ). Moreover, the activation of macrophage can be inhibited by fucose, and it is an important regulator of intestinal mucosal immunity ( 51 ). Fucose plays a critical role in mucosal immunity through its immunocompetence of anti-infection and anti-inflammation ( 52 ), which is of great significance to prevent the occurrence and progression of IgAN from the pathogenesis.…”
Section: Discussionmentioning
confidence: 99%